Right-wing populism in 21st century Portugal - Marchi, R. (Spring research school facing the global turmoil. Updating traditions, puzzling the future, 2022)
Universidade Lusófona Sam Nunn School of International Affairs (Georgia, USA) and the Observatório Político (OP, Universidade Lusofona) 20 May 2022